2002
DOI: 10.1128/mcb.22.21.7581-7592.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Retention of Phosphorylated Extracellular Signal-Regulated Kinase and a Rho-Associated Kinase-Mediated Signal Impair Expression of p21Cip1/Waf1 in Phorbol 12-Myristate-13- Acetate-Induced Apoptotic Cells

Abstract: In response to treatment with phorbol-12-myristate-13-acetate (PMA), the half-population of erythromyeloblast D2 cells, a cytokine-independent variant of TF-1 cells, displayed adhesion and differentiated into a monocyte/macrophage-like morphology, while the other half-population remained in suspension and underwent apoptosis. Expression of the cell cycle inhibitor p21Cip1/Waf1 was induced after PMA treatment in the adherent cells but not in the proapoptotic cells. We investigated the mechanism responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 60 publications
4
34
1
1
Order By: Relevance
“…As such the protective effect against growth factor depletion is carried out by cytoplasmic ERK, whereas the anti-apoptotic response against STI571 takes place in the nucleus. In line with our data, in D2 myeloid cells phosphorylated ERK accumulates in the cytoplasm of phorbol ester-induced pro-apoptotic cells (63), and recent results indicate that PEA-15, a protein that retains activated ERK in the cytoplasm, can prevent tumor necrosis factor ␣-induced apoptosis in astrocytes (64). On the other hand, we show that constitutive ERK activation, irrespective of its localization, is insufficient to prevent apoptosis induced by stimuli such as UV light, probably as a consequence of the apoptogenic response against this type of radiation being primarily unleashed by processes that occur downstream from ERKs.…”
Section: Discussionsupporting
confidence: 78%
“…As such the protective effect against growth factor depletion is carried out by cytoplasmic ERK, whereas the anti-apoptotic response against STI571 takes place in the nucleus. In line with our data, in D2 myeloid cells phosphorylated ERK accumulates in the cytoplasm of phorbol ester-induced pro-apoptotic cells (63), and recent results indicate that PEA-15, a protein that retains activated ERK in the cytoplasm, can prevent tumor necrosis factor ␣-induced apoptosis in astrocytes (64). On the other hand, we show that constitutive ERK activation, irrespective of its localization, is insufficient to prevent apoptosis induced by stimuli such as UV light, probably as a consequence of the apoptogenic response against this type of radiation being primarily unleashed by processes that occur downstream from ERKs.…”
Section: Discussionsupporting
confidence: 78%
“…Rho kinase's proapoptotic role may be mediated via regulation of actin cytoskeletal rearrangement, which in turn induced the activation of the caspase cascade via the assembly of the deathinducing signaling (28,29,33,34). In addition, we demonstrated that constitutively active ROCK-1 generated by cleavage was sufficient to activate caspase-3 and lead to myocyte apoptosis, as outlined in a schematic model (Fig.…”
Section: Caspase-3 Activation By Rock⌬1 Induced Pten Activation and Aktmentioning
confidence: 83%
“…ROCK-mediated MLC phosphorylation acts as an upstream event required for membrane contraction and the subsequent caspase 8, 10 and 3 activation during phorbol-12-myristate-13-acetate (PMA) stimulation in erythroblastic TF-1 cells [67]. In addition to MLC phosphorylation, ROCK activation mediates other molecular events in PMA-treated apoptotic cells such as prevention of nuclear distribution of phospho-ERK, inhibition of induction of the cell cycle inhibitor p21 (Cip1/Waf1) [68], and cytosolic translocation of heterogeneous nuclear ribonucleoprotein C1 and C2, which are two nuclear restricted pre-mRNA binding proteins [72]. In primary thymocytes, apoptosis induced by activation of the receptor for thromboxane A(2), which is coupled to Gα(12/13) subunits, is inhibited by deletion of Lsc RhoGEF (an activator of GTPases of the Rho family), associated with inactivation of Rho/ROCK and increased Akt phosphorylation [47].…”
Section: In Vitro Evidencementioning
confidence: 99%